1997
DOI: 10.1046/j.1365-2958.1997.3741745.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive Salmonella typhimurium mutants are avirulent because of an inability to enter and destroy M cells of ileal Peyer's patches

Abstract: Salmonella typhimurium initiates infection of a host by invading M cells of Peyer's patches within the small intestine. The ability of the bacteria to invade mammalian cells has been shown to be regulated by environmental conditions, including oxygen concentrations, osmolarity, and growth phase. We have previously created oxygen-regulated Tn5lacZY S. typhimurium mutants that are defective in invasion. We have now identified the invasion genes disrupted by eight of the transposon insertions. These genes encode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
155
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(168 citation statements)
references
References 35 publications
9
155
1
1
Order By: Relevance
“…HA and HR serotypes may be permitted to give raise to a systemic infection provided they interact with a unique character of a specialized tissue of the host epithelium. This hypothesis is supported by the observation that, although the majority of salmonella epithelial cell interactions occur at the apical membrane of the enterocytes [147], early association and entry of salmonella appears to be via the M cells lining the small intestine PP [57,[170][171][172][173]. Cytokine secretion by M cells and activation of subepithelial phagocytic cells may regulate both intestinal inflammation and salmonella persistence in deeper tissues.…”
Section: Site Of In Asionmentioning
confidence: 97%
“…HA and HR serotypes may be permitted to give raise to a systemic infection provided they interact with a unique character of a specialized tissue of the host epithelium. This hypothesis is supported by the observation that, although the majority of salmonella epithelial cell interactions occur at the apical membrane of the enterocytes [147], early association and entry of salmonella appears to be via the M cells lining the small intestine PP [57,[170][171][172][173]. Cytokine secretion by M cells and activation of subepithelial phagocytic cells may regulate both intestinal inflammation and salmonella persistence in deeper tissues.…”
Section: Site Of In Asionmentioning
confidence: 97%
“…A serovar Typhimurium orgA::Tn5lacZY mutant is noninvasive and has reduced virulence for mice following oral infection. Other work has shown that this mutation prevents the invasion and destruction of M cells and has a general defect in secretion of invasion effector proteins (43). In addition, orgA is similar to the mxiK gene in Shigella (1), a putative component of the type III secretion system in that pathogen.…”
mentioning
confidence: 91%
“…Salmonella enterica serovar Typhimurium mutants that are unable to invade tissue culture cells are defective in their ability to invade and destroy M cells (26,43). This defect severely limits the ability of the bacteria to initiate infection and reduces their virulence in mice (14,24,43).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonellae express a variety of virulence factors, including very polymorphic surface carbohydrates, multiple fimbrial adhesins, phase-variable flagella, and mechanisms for invasion and survival in host macrophages and other cells (see review in references 13 and 44). Because Salmonella is acquired mainly by oral ingestion of contaminated materials, a key step of infection is its passage across the intestinal epithelium by invasion of M cells in Peyer's patches (7,20,39) or of enterocytes (46). Many of the genes required for intestinal penetration and invasion of host cells are carried on the 40-kb region at centisome 63, which is called Salmonella pathogenicity island 1 (SPI1) (reviewed in reference 10).…”
mentioning
confidence: 99%